Complications of Coronavirus Disease-19 in a Hospitalized Patient: A Case Report - Meshkova, Iskra; Mijakoski, Dragan; Simeonova, Magdalena; Markovska, Zorica; Markoska, Vesna (Scientific Foundation Spiroski (publications), 2020)
BACKGROUND: Coronavirus (CoV) disease (COVID)-19 infection is a major public health issue worldwide with no specific therapy or vaccine. CASE REPORT: COVID-19-positive patient was hospitalized due to a dry irritating cough that has persisted for 3 days. The polymerase chain reaction test to severe acute respiratory syndrome-CoV-2 was positive. Computed tomography (CT) scan of the lungs showed massive bilateral consolidation. The patient was set to oxygen support (6 L/min). Two hours after referring the patient’s condition worsened with shortness of breath, suffocation, wheezing, and decreased saturation (77%). The patient was given mechanical support with continuous positive airway pressure mask. Therapy included azithromycin 500 mg and ceftriaxone 2 g. On the 3rd day of hospitalization, there was a sharp deterioration of the condition and a decrease in saturation (40%). The patient was intubated and immediately placed on intermittent positive pressure ventilation. Azithromycin was now combined with meropenem 3 × 1 g. The next morning patient’s condition further worsened with decrease in saturation and heart rate. The resuscitation was unsuccessful. CONCLUSION: COVID-19 is primary a respiratory infection, but the virus also affects other organs with poor outcome.
Keywords: pandemics; intensive care; lungs; corona virus infection; treatment; SARS-CoV-2; prevention